الصناعة في العراق في العصر العباسي الأخير552 ـ 656 هـ / 1157 ـ 1258 م (مجلة ابحاث كلية التربية الاساسية, 2010)
ملخص البحث :شهد العراق في العصر العباسي الأخير تطوراً ملحوظاً في نشاطه الصناعي ، إذ ساعد ذلك توافر المواد الأولية المتنوعة ، فضلاً عن النشاط التجاري الذي وفّر ما كانت تحتاجه الصناعة من مواد أولية ، فقامت صناعات متعددة شملت مختلف المدن التي اختصت كل منها بصناعة معينة اشتهرت بها ، كل ذلك ساعد على ازدهار الصناعة على المستويين الداخلي والخارجي بحيث وصل المنتوج العراقي إلى أقاليم مختلفة من العالم .Iraq witnessed in the latest abbasid era, a prominent development in its industrial activity. This helped in the availability of various raw materials , as well as the commercial activity that provided what the industry needed from raw materials. Many industries have been arise which included different cities each one of which specialized in specific industry. All of this helped the industry prosperity on the internal and external levels which made the Iraqi product reached different provinces of the world .